Framework for ontology-based Negotiation to support enterprise interoperability in cloud-based environments - Cretan, A.; Ferreira da Silva, C.; Coutinho, C.; Jardim-Goncalves, R.; Ghodous, P. (International Journal of Electronic Business Management, 2013)
In the actual competitive and global business context, the maintenance of interoperation among heterogeneous organisations in a collaborative environment becomes difficult to achieve. Hence, in a dynamic context a change in any of the networked partners affects the others, creating difficulties to sustain the interoperability of the networked environment. This paper proposes negotiation as a key mechanism to achieve and maintain the interoperability between the organisations’ systems and applications, as a supporter for the conflict resolution that typically occurs when the different players discuss and analyse the potential solutions for the interoperation of the integrated business environment. Thus, the presented approach tackles the issue of semantic heterogeneity by introducing ontologies as the main support in the negotiation process. In this respect, this paper proposes an ontology-enriched negotiation framework for sustainable Enterprise Interoperability (EI) and its validation in an industrial scenario. To allow a sustainable, flexible and generic approach towards the infrastructure implementation in global scale, a cloud web-service-based platform is proposed for setting of the framework.